Jancuk : Public perceptions on the use of swear words in communication among Arek cultural community in East Java - Ahmadintya Anggit Hanggraito (Airlangga University, 2021)
Jancuk is a swear word and has become part of the cultural communication of arek in East Java, Indonesia. This research tries to analyze the perception and meaning of jancuk from Indonesian society. This research is a descriptive research through a qualitative approach. 121 representative respondents were obtained through purposive sampling. Then, the data will be triangulated to draw conclusions and recommendations. The results showed that the period of education and growth became the jancuk word’s absorption phase. The results of the analysis explain that Jancuk is not perceived negatively. Its depends on the intensity of emotion in communication. However, Jancuk is still perceived as a word that violates politeness in the communication process. Then, the main meaning of jancuk consists of: humiliation, annoyance, disappointment, surprise, and a symbol of intimacy or humor. Based on this research, the perception of words in a particular culture can be seen as an expression that has various meanings. It is expected that this research will provide the reason for the public that jancuk can be an important contributor to the process of enriching social cross-cultural communication materials.